Determination of Planning Target Volume (PTV) Margins Using Redefined Systematic and Random Error Equations from Single-Fraction Verification Data: A Case Study of Cervical Cervic - Lestari, Tuti; Muttaqin, Afdhal; Hanisti, Fidhia; Diyona, Fiqi (Diponegoro University Semarang Indonesia, 2025)
This study aimed to determine the Planning Target Volume (PTV) margin by redefining the equations for systematic and random errors in a cervical cancer case. The research utilized first-fraction radiotherapy position verification data from 37 cervical cancer patients. These data comprised planned and actual positions, with the difference interpreted as the position shift. The systematic and random error equations proposed by the Royal College of Radiologists (2008) were redefined by adapting them to verification data, which were grouped into several PTV types and treated as daily fractions. The PTV margin was then calculated using formulas by Van Herk (2004), Stroom (2002), and ICRU Report 62. The results showed that the largest systematic and random errors occurred in the vertical and longitudinal directions, measuring 0.83 cm and 1.71 cm, respectively. The PTV margin calculated using the Van Herk method was comparatively larger than those obtained using the other two methods. The percentages of position shifts that exceeded the calculated PTV margins in the vertical, longitudinal, and lateral directions were 16%, 43%, and 35%, respectively. These findings indicate that the redefined equations are capable of compensating for the lack of position shift data across all radiotherapy fractions. The redefined approach can provide a more accurate estimation of PTV margins in cervical cancer treatment using single-fraction verification data.